Preaching in the Millennial Era Through the Song "Jakarta Today" by For Revenge - Khumaedi, Teddy; Elma Fitriani, Nanda (Ath Thariq Jurnal Dakwah dan Komunikasi, 2024)
The song Jakarta Hari Ini is a song that went viral again in 2023, this song has a da'wah message contained in the lyrics. The purpose of this study is to explain how the message of da'wah is contained in the song Jakarta Hari Ini. To obtain the results of this study, the author used a qualitative descriptive method by reading, recording and understanding the lyrics of the song. The results of this study show that the message of da'wah in the song Jakarta Hari Ini is to remind people who hate something even though it is very people good for them. Human who likes something but it's bad for him. This is due to the tendency of lust for beliefs or desires that will inevitably harm him and his unwillingness to perform taklif or tasks that will make him happy which is described in Surah Al Baqarah verse 216. In addition, the emphasis of the content of the The song's message is a lot of awareness of human understanding in doing their deeds. This song also invites the listener not to dissolve in sadness sadness over the calamity has befallen him.